Half a century of dynamic instability following the ocean-driven break-up of Wordie Ice Shelf - Dømgaard, Mads; Millan, Romain; Andersen, Jonas K.; Scheuchl, Bernd; Rignot, Eric; Izeboud, Maaike; Bernat, Maud; Bjørk, Anders A. (Nature communications, 2025)
Ice shelves restrain grounded ice discharge into the ocean, and their break-up contributes significantly to Antarctica’s sea level rise. Using aerial imagery from the 1960s and modern satellite data, we construct a long-term record of Wordie Ice Shelf’s disintegration and its effects on tributary glaciers. Early changes in pinning points and ocean warming in Marguerite Bay since the 1960s strongly suggest increasing basal melt as the primary driver of the ice shelf disintegration. Some glaciers responded immediately to the ice shelf break-up, with surface velocities tripling, thinning up to 160 m, and grounding line retreat of 7.5 km, while others reacted decades later due to buttressing from remnant parts of the ice shelf. Our findings emphasize the importance of long-term observations to understand ice shelf disintegration and its impacts, offering crucial insights for assessments of future ice loss from the Antarctic Ice Sheet. Historical images show that Antarctica’s Wordie Ice Shelf has disintegrated due to rising basal melt since the 1960s, causing varied glacier responses and highlighting the need for long-term observations to improve predictions of Antarctic ice loss.